New Approaches to Defense Inflation and Discounting - Connor, Kathryn (RAND Corporation, 2013)
To assess how well current inflation indices and discount rates serve weapon-system program management, this study investigates inflation rates for parts for the Abrams and Bradley ground vehicles. Because even similar systems experience inflation differently, estimating strategies should be reviewed annually to reflect changing costs, and analysis of investments should be expanded to ensure consideration of least-cost outcomes.